Prevalence and causes of blindness and low vision in Timor-Leste. Issue 9 (20th August 2007) - Ramke, Jacqueline; Palagyi, Anna; Naduvilath, Thomas; du Toit, Renee; Brian, Garry
Abstract : Aim: To estimate the prevalence and causes of blindness and low vision in people aged ⩾40 years in Timor-Leste. Method: A population-based cross-sectional survey using multistage cluster random sampling to identify 50 clusters of 30 people. A cause of vision loss was determined for each eye presenting with visual acuity worse than 6/18. Results: Of 1470 people enumerated, 1414 (96.2%) were examined. The age, gender and domicile-adjusted prevalence of functional blindness (presenting vision worse than 6/60 in the better eye) was 7.4% (95% CI 6.1 to 8.8), and for blindness at 3/60 was 4.1% (95% CI 3.1 to 5.1). The adjusted prevalence for low vision (better eye presenting vision of 6/60 or better, but worse than 6/18) was 17.7% (95% CI 15.7 to 19.7). Gender was not a risk factor for blindness or low vision, but increasing age, illiteracy, subsistence farming, unemployment and rural domicile were risk factors for both. Cataract was the commonest cause of blindness (72.9%) and an important cause of low vision (17.8%). Uncorrected refractive error caused 81.3% of low vision. Conclusion: Strategies that make good-quality cataract and refractive error services available, affordable and accessible, especially in rural areas, will have the greatest impact on vision impairment.